IMPLIKASI KEBIJAKAN HARGA BBM TERHADAP POLA KONSUMSI DAN KESEJAHTERAAN MASYARAKAT: STUDI KASUS LINGKUNGAN 3, KELURAHAN AUR, MEDAN MAIMUN (2004-2014) - Lestari Dara Cinta Utami Ginting; Rahman Malik; Lila Pelita Hati (Bajang Institute, 2024)
The fuel price policy during the 2004-2014 administration of President Susilo Bambang Yudhoyono (SBY) has become a major concern in the social and economic context of society. The policy has undergone several price adjustments during his 10-year administration, which significantly affected the price of basic necessities and the consumptive lifestyle of the community. This study aims to analyze the implications of the fuel price policy on consumption patterns and socio-economic welfare of slum communities in Lingkungan 3, Kelurahan Aur, Medan Maimun, in the 2004-2014 period. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and analysis of related documents. The results showed that the fuel price increase policy during SBY's administration had a significant impact, especially on low-income communities. Despite the increase in fuel prices, the level of community consumption focused on basic needs, but also included electronic goods such as televisions, refrigerators, and cellphones. In addition, the consumption pattern of electronic goods in slum communities in Neighborhood 3, Kelurahan Aur, Medan Maimun, for the period 2004-2014 shows the existence of luxuries in household appliances despite low income. This indicates that the consumptive culture of the community in Neighborhood 3 tends to be high, but the spirit for a better life is not evident from efforts to save or divert expenditure to long-term investment. In conclusion, the SBY administration's fuel price policy has complex implications for the level of community consumption, especially in relation to electronic goods. This shows the need for special attention in managing fuel price policy so that it does not only have an impact on the state's fiscal aspects, but also pays attention to social impacts, especially for low-income people